Age and gender influence on clinical manifestations of thyroid-associated ophthalmopathy: a case series of 2479 Chinese patients - Yang, Mei; He, Weimin (Frontiers in Endocrinology, 2024)
Background: Significant individual differences exist in the clinical manifestations of thyroid-associated ophthalmopathy (TAO). Age and gender have an impact on the presentation and severity of TAO.Objective: To evaluate the clinical characteristics of TAO patients, with particular consideration of their age and gender.Methods: Demographic and clinical data of 2479 TAO patients were collected. Patients were divided into 7 groups based on age: Group 1: ≤18 years old; Group 2: 19-29 years old; Group 3: 30-39 years old; Group 4: 40-49 years old; Group 5: 50-59 years old; Group 6: 60-69 years old; Group 7: ≥70 years old. Compared clinical manifestations among different groups and between males and females.In age group 1, the ratio of female to male TAO patients was 3.79, and in age group 7, it was 0.86. As age increased, there was a decline in the percentage of females (γ=-0.168, P＜0.001). During the aging process, the proportion of TAO patients with unilateral involvement also gradually decreased (γ=-0.23, P ＜ 0.001). In addition, the proportion of TAO patients with upper eyelid retraction ≥2mm and exophthalmometry ≥17mm also decreased (γ=-0.158, P ＜ 0.001, γ=-0.23, P ＜ 0.001). In comparison to males, females with TAO showed a higher proportion of unilateral eye involvement and upper eyelid retraction ≥2mm (P=0.038, P ＜ 0.001). However, males had a higher proportion of exophthalmometry ≥17mm (P ＜ 0.001). The proportions of patients with eye movement disorder (γ=0.535, P<0.001), diplopia (γ=0.446, P<0.001), intraocular pressure (IOP) ≥30mmHg (γ=0.149, P<0.001), sight-threatening TAO (γ=0.479, P<0.001), and active TAO (γ=0.469, P<0.001) were positively correlated with age in TAO patients. Additionally, the proportion of male patients is higher than that of female patients.TAO Patients exhibit different clinical features depending on age and gender. In elderly and male patients, TAO tends to be more severe, with a higher prevalence of eye muscle involvement, IOP ≥30mmHg, active phases, and a lower proportion of patients with upper eyelid retraction ≥2mm.Elderly female patients also have a lower proportion of exophthalmometry ≥17mm.